POLIGAMI DI DUNIA ISLAM - Hakim, Abdurrahman; Aibak, Kutbuddin (Ahkam: Jurnal Hukum Islam, 2021)
This paper compares the legal verses of polygamy in Saudi Arabia, Pakistan, and Indonesia. Apart from the controversy considered as detrimental and degrading to women, term of polygamy is not as easy as Westerners think in the license process. This study compares legal verses, licensing procedures, fines, either imprisonment or punishment, to husbands who violate the applicable regulations. Therefore, this research serves as evidence talthough polygamy is permitted, the procedures and requirements regulated by Saudi Arabia, Pakistan, and Indonesia contain elements of protection and respect for women. The method is qualitative with the library type. This research is classified as a co-comparative approach, which is a study that compares one legal case between several countries. The results are: 1) in Saudi Arabia, polygamy is still based on the classical Islamic fiqh school of Imam Hambali. Therefore, polygamy is not so much a concern in parliament that there is no legal reform there. As a result, polygamy is very free and tends to harm women. 2) in Pakistan, polygamy is also based on Islamic teachings, it's just that there is a legal reform that states that there must be written permission from the Arbitration Council if a husband wants to do polygamy. 3) in Indonesia, polygamy is very complicated, because basically the Marriage Law No. 16 of 2019 concerning Marriage contains the principle of monogamy. In addition, polygamy can be carried out by the husband if he has received permission from the wife and the board of judges in court.